Desenvolvimento e caracterização de sensores eletroquímicos modificados com meso-tetra-(2-tienil)- porfirinato de cobre (II) para a determinação de dopamina em amostras biológicas sintéticas - Fava, Elson Luiz (Universidade Federal de São Carlos, 2016)
In this work, was built gold (Au) and glassy carbon (GC) electrochemical sensors modified with cooper (II) meso-tetra-(2-thienyl)-porphyrinate ([Cu(II)TThP]) and the GC modified electrode was applied for dopamine determination. For this, they where evaluated the gold electrode and glassy carbon electrode as substract and for electrode modification, was studied the drop coating (for gold electrode) and oxidative electropolymerization (for both electrodes) procedures. Studies based on the use of gold electrode did not obtain satisfactory results, however, the search for the optimization of an appropriate modification procedure led to studies on the electronic properties and electrochemical of [Cu(II)TThP]. Thus, studies were made of the redox processes of this compound by cyclic voltammetry, using molecules with similar groups for comparison and subsequent allocation of anodic and cathodic peak obtained for [Cu(II)TThP]. In addition, it performed tests by spectrophotometry UV-Visible for the compounds used in the electrochemical assay, thus knowing the electronic contribution of the complexed metal of the porphyrin ring and thiophene groups. Thus, electropolymerization of [Cu(II)TThP] on the glassy carbon electrode was carried out using the technique of cyclic voltammetry, monitoring the formation of layers of poly-[Cu(II)TThP] using the observed current increment done every cycle. The formation of the polymer film on the glassy carbon electrode was confirmed by morphological characterization studies, obtaining images by electron microscopy high resolution scan and Raman spectroscopy. From Cyclic voltammetry studies conducted to dopamine, one constant high heterogeneous electron transfer was diagnosed (2.73 × 10−3 cm s−1) for the poli-[Cu(II)TThP] electrode, where compared with glassy carbon electrode (3.53 × 10−4 cm s−1) showing good electrochemical performance of the proposed sensor. Then, volumetric methods for the determination of dopamine was developed. Using the square wave voltammetry technique (SWV) under optimized conditions, the analytical curves for dopamine was linear in the range of 0.0575 to 4.091 μmol L−1, with a 40.9 nmol L−1 for limit of detection. The proposed voltammetric procedure was efficiently applied to determine dopamine synthetic biological samples (urine and human serum).
Development of electrochemical sensors modified with cooper (II) meso-tetra-(2-thienyl)-porphirinate for determination of dopamine in biological samples
Keywords: Sensores modificados com porfirinas; Porfirinas; Eletropolimerização; Dopamina; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA